Answer:
Final answer is [tex]g\left(x\right)\cdot f\left(x\right)=\frac{\left(x-6\right)}{2x\left(x+3\right)}[/tex].
Step-by-step explanation:
given functions are [tex]f(x)=x-6[/tex] and [tex]g\left(x\right)=\frac{1}{2x\left(x+3\right)}[/tex].
Now we need to find about what is the value of [tex]g\left(x\right)*f\left(x\right)[/tex].
[tex]g\left(x\right)*f\left(x\right)[/tex] simply means we need to multiply the value of [tex]f(x)=x-6[/tex] and [tex]g\left(x\right)=\frac{1}{2x\left(x+3\right)}[/tex].
[tex]g\left(x\right)\cdot f\left(x\right)=\frac{1}{2x\left(x+3\right)}\cdot\left(x-6\right)[/tex]
[tex]g\left(x\right)\cdot f\left(x\right)=\frac{\left(x-6\right)}{2x\left(x+3\right)}[/tex]
Hence final answer is [tex]g\left(x\right)\cdot f\left(x\right)=\frac{\left(x-6\right)}{2x\left(x+3\right)}[/tex].